4. Reliability of the perturbational complexity index in discriminating chronic patients with disorders of consciousness. Issue 1 (January 2015) - Fecchio, M.; Casarotto, S.; Trimarchi, P.D.; Casali, A.G.; Landi, C.; Pigorini, A.; Saia, L.; Napolitani, M.; Sarasso, S.; Rosanova, M.; Devalle, G.; Massimini, M.
<x xml:space="preserve">Abstract</x> The level of consciousness is normally assessed based on the ability of an individual to interact with the surrounding environment and communicate. Theoretically, consciousness is thought to rely on brain complexity (i.e., joint presence of functional integration and functional differentiation). Transcranial magnetic stimulation combined with electroencephalography (TMS/EEG) has been recently proposed as a neurophysiological tool able to gauge the conjoint presence of integration and information in physiological and pathological conditions. Here we tested the reliability of the algorithmic complexity of TMS-evoked potentials (Perturbational Complexity Index, PCI) by comparing PCI with the Coma Recovery Scale-Revised (CRS-R) in sixty chronic brain-injured patients (22 vegetative state-VS, 25 minimally conscious state-MCS, 13 conscious state-CS) with a stable clinical diagnosis. CRS-R was significantly lower in VS as compared to MCS and CS groups. Interestingly, PCI invariably discriminated between VS and MCS/CS conditions at the single-patient level. Although preliminary, our results suggest that PCI may serve as a valuable tool to discriminate VS and MCS/CS conditions also when the behavioral evaluation gives ambiguous indications. Future studies should further validate PCI in discriminating VS from MCS/CS by involving larger samples and by comparing it with other brain functional assessments, e.g., event-related potentials and/or functional magnetic resonance imaging.